Mixed-breed guarding dogs reduce conflict between goat herders and native carnivores in Patagonia - González, Alejandro (2012)
Goat husbandry is the main rural livelihood in the northern Patagonian steppe of Argentina, and herders kill any carnivore that they believe threatens their herds, including the endangered Andean cat (Leopardus jacobita). We evaluated the use of local, medium-sized, mixed-breed guarding dogs to reduce predation and retaliatory killing of carnivores. We interviewed 64 herders, and delivered 37 puppies to 25 herders. Most economic loss was attributed to cougars (Puma concolor) and culpeos (Lycalopexculpaeus). All herders with dogs that reached the working stage reported reduced rates of predation, and 88% reported that they no longer kill carnivores. Among herders who were not using dogs, 89% of them reported increased predation, and 100% of them confi rmed that they kill carnivores. Mixed-breed dogs can be effective in reducing both predation losses and retaliatory killing, but their success depends on the ability and willingness of herders to train and use them properly.